Application of Multi-Criteria Decision-Making Process to Select Waste-to-Energy Technology in Developing Countries : The Case of Ghana - Agbejule, Adebayo; Shamsuzzoha, Ahm; Lotchi, Kodjovi; Rutledge, Kendall (MDPI, 2021)
Municipal solid waste (MSW) in the Accra region of Ghana has created the need for innovative ways to deal with waste management crises facing the city. The goal of this study is to use the analytical hierarchy process (AHP) to select an appropriate waste-to-energy (WtE) technology for Accra. The AHP methodology is used to assess four WtE technologies, namely landfill biogas, incineration, anaerobic digestion, and aerobic composting. Three main criteria and nine sub-criteria are identified for pair-wise comparison and assessed by 10 experts. The results show that incineration is the most preferred technology, followed by anaerobic digestion and aerobic digestion, with landfilled gas being the least preferred technology. Stakeholders in waste management development in Ghana can utilize the findings of the study to develop implementation strategies for capacity and institutional capabilities for both thermochemical and biochemical processes in the country.
Keywords: AHP; mega city; Accra; case study; waste-to-energy; fi=Tuotantotalous|en=Industrial Management|